2014
DOI: 10.1371/journal.pone.0090284
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Induces an Expanded Range of Downstream Genes in Reconstituted Human Epidermis Model

Abstract: BackgroundIL-17 is the defining cytokine of the Th17, Tc17, and γδ T cell populations that plays a critical role in mediating inflammation and autoimmunity. Psoriasis vulgaris is an inflammatory skin disease mediated by Th1 and Th17 cytokines with relevant contributions of IFN-γ, TNF-α, and IL-17. Despite the pivotal role IL-17 plays in psoriasis, and in contrast to the other key mediators involved in the psoriasis cytokine cascade that are capable of inducing broad effects on keratinocytes, IL-17 was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
161
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 57 publications
5
161
0
Order By: Relevance
“…MCPIP1 activity has been linked to many diferent biological processes within various cell types, such as inhibition of inlammation, angiogenesis, cell migration, or cell diferentiation [56], but no prior evidence of MCPIP1 expression and function in the skin had been reported. In this study, MCPIP1 expression was found to be aberrantly expressed by suprabasal keratinocytes of psoriasis lesions, which is consistent with the distribution of that described for IL-17RA in the psoriatic epidermis [57,58]. In this regard, only diferentiating keratinocytes isolated from psoriatic lesional skin, but not from healthy skin, were susceptible to undergo an increased Human Translational Research in Psoriasis Using CLA+ T Cells http://dx.doi.org/10.5772/67815 67 expression of MCPIP1 to exogenous IL-17A.…”
Section: An Interdisciplinary Approach To Psoriasis 66supporting
confidence: 90%
“…MCPIP1 activity has been linked to many diferent biological processes within various cell types, such as inhibition of inlammation, angiogenesis, cell migration, or cell diferentiation [56], but no prior evidence of MCPIP1 expression and function in the skin had been reported. In this study, MCPIP1 expression was found to be aberrantly expressed by suprabasal keratinocytes of psoriasis lesions, which is consistent with the distribution of that described for IL-17RA in the psoriatic epidermis [57,58]. In this regard, only diferentiating keratinocytes isolated from psoriatic lesional skin, but not from healthy skin, were susceptible to undergo an increased Human Translational Research in Psoriasis Using CLA+ T Cells http://dx.doi.org/10.5772/67815 67 expression of MCPIP1 to exogenous IL-17A.…”
Section: An Interdisciplinary Approach To Psoriasis 66supporting
confidence: 90%
“…Plasmin has been shown to be involved in wound healing by promoting migration of epidermal keratinocytes coupled with enhanced phagocytic-killing and inhibition of proliferation, which may facilitate re-epithelialization following skin injury [68] and has been shown to play a role in the amplification of psoriasiform skin inflammation in mice [69]. H 2 O 2 has been demonstrated to be involved in wound healing [70], UV-induced DNA damage in keratinocytes [71], and skin blanching [72], IL-17 is a critical component of the Il-17/Il-23 pathway, which is involved skin inflammation and pathogenesis of psoriasis [73][74][75][76]. TGFβ1 has been shown to be involved in control of wound healing and inhibition of keratinocyte proliferation [77].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the addition of a cytokine cocktail, normal 3Dskin equivalent can adapt a psoriasis-like phenotype and gene expression profile. Previous studies revealed that IL-22 or a mixture of IL-17, IL-22 and TNF-α triggered hyperplasia in normal 3D skin equivalent, with a reduced expression of differentiation-related genes and up regulation of psoriasis markers [12]. Full thickness skin equivalents, which have functional dermal matrix and fibroblasts, are more similar to human skin.…”
Section: Three-dimensional (3d) Psoriasis Skin Modelmentioning
confidence: 99%